2020
DOI: 10.1016/j.isci.2019.100790
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction of USP14 with the Chaperone HSC70 Mediates Crosstalk between the Proteasome, ER Signaling, and Autophagy

Abstract: SummaryUSP14 is a deubiquitinating enzyme associated with the proteasome important for protein degradation. Here we show that upon proteasome inhibition or expression of the mutant W58A-USP14, association of USP14 with the 19S regulatory particle is disrupted. MS-based interactomics revealed an interaction of USP14 with the chaperone, HSC70, in neuroblastoma cells. Proteasome inhibition enhanced binding of USP14 to HSC70, and to XBP1u and IRE1α proteins, demonstrating a role in the unfolded protein response. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Indeed, very little is known about the effects of an enhanced UPS activity on the autophagy flux and consequent rate of protein degradation. In the context of huntingtin metabolism, recent studies unraveled a role for the deubiquitinase ubiquitin specific peptidase 14 (USP14) as a common denominator mediating a compensatory negative feedback between the two major proteolytic pathways [176][177][178]. On the one hand, UPS activation achieved through USP14 inhibition facilitates the clearance of tau and reduces the amount of its oligomeric forms.…”
Section: Huntingtinmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, very little is known about the effects of an enhanced UPS activity on the autophagy flux and consequent rate of protein degradation. In the context of huntingtin metabolism, recent studies unraveled a role for the deubiquitinase ubiquitin specific peptidase 14 (USP14) as a common denominator mediating a compensatory negative feedback between the two major proteolytic pathways [176][177][178]. On the one hand, UPS activation achieved through USP14 inhibition facilitates the clearance of tau and reduces the amount of its oligomeric forms.…”
Section: Huntingtinmentioning
confidence: 99%
“…This may occlude the degradation of large, non-proteasomal substrates. Potential mechanistic insights on the role of UPS14 in the coordinated activities between UPS and autophagy were also provided [178]. In detail, UPS inhibition disrupts the association of USP14 with the P19S regulatory particle of the UPS, while fostering its interaction with either the autophagy protein GABARAP or the heat-shock-related co-chaperonin HSC70 [178].…”
Section: Huntingtinmentioning
confidence: 99%
See 2 more Smart Citations
“…In eukaryotes, XBP1u mRNA can still be translated into a protein with less stability that is rapidly degraded by the ubiquitin-proteasome system (Navon et al, 2010 ). Our recent work showed that proteasome inhibition, stabilizing the protein, resulted in the formation of XBP1u aggresome like induced structures in neuronal cells (Srinivasan et al, 2020 ). The role of these XBP1u structures in neuronal IRE1α signaling remains to be explored.…”
Section: Ire1α Signalingmentioning
confidence: 99%